Eficácia e sensibilidade dental resultante do clareamento dental de consultório com 6¢ H2O2/TiO_N. Estudo clínico randomizado controlado - Bortolatto, Janaína Freitas [UNESP] (2014)
This study compared the efficacy and tooth sensitivity resulting from use of a bleaching agent composed of 6% hydrogen peroxide containing nanoparticles of nitrogen-doped titanium dioxide (PH6) with a traditional bleaching agent containing 35% hydrogen peroxide (PH35); both agents were activated by a hybrid LED/Laser light. 48 volunteers between 18 and 28 years of age participated in this randomized, controlled, triple-blinded clinical study with paired samples. They were randomly divided in 2 groups: PH6 (test) and PH35 (control). Two clinical sessions were performed with an interval of 7 days between them. In each session, two consecutive applications of the bleaching agent were performed. In each of them, the bleaching agent was applied for 12 minutes, activated intermittently for half of the duration. Efficacy (E) was determined by color alteration (ΔE), recorded with reflectance spectroscopy. It was assessed at T0 (baseline), after the 1st. bleaching session (T1) and after the 2nd. session (T2). Tooth sensitivity (S) was characterized according to Occurrence (OS), Intensity (IS), Type (TS) and Duration (DS). Efficacy was analyzed by repeated measures ANOVA and post hoc Bonferroni test and tooth sensitivity was analyzed descriptively and inferentially by means of chi-squared test (α=0.05). 23 The tests showed significantly higher values of ΔE for PH35 in T2. For PH6, bleaching was the same in both sessions. PH35 showed a higher occurrence of sensitivity than PH6. Intensity and duration of sensitivity were greater for the PH35 group. The majority of volunteers classified the type of pain experienced in their sensitivity in the form of a shock. For patients aged between 18 and 28 years old, PH35 promoted higher tooth bleaching and greater sensitivity than PH6. PH6 should be the option of choice for dental office bleaching.